1994
DOI: 10.1016/s0741-5214(94)70003-6
|View full text |Cite
|
Sign up to set email alerts
|

Protecting the ischemic spinal cord during aortic clamping: The influence of selective hypothermia and spinal cord perfusion pressure

Abstract: Selective deep hypothermia of the spinal cord prevents paraplegia after 45 minutes of double aortic clamping in dogs. Cerebrospinal fluid drainage was not effective in preventing paraplegia in this model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(14 citation statements)
references
References 26 publications
0
14
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8] In many SCI animal protocols, the aorta is cross-clamped to interrupt intercostal or lumbar arterial perfusion, because the small aortic branches are so numerous and ligating or clamping them is complicated. In canine SCI experimental models, the thoracic aorta is occluded in a manner mimicking the operative condition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5][6][7][8] In many SCI animal protocols, the aorta is cross-clamped to interrupt intercostal or lumbar arterial perfusion, because the small aortic branches are so numerous and ligating or clamping them is complicated. In canine SCI experimental models, the thoracic aorta is occluded in a manner mimicking the operative condition.…”
Section: Discussionmentioning
confidence: 99%
“…As documented in the previous reports on SCI experiments using dogs, aortic cross-clamping alone (CL) or aortic occlusion associated with proximal-to-distal aortic bypass (CL-AB) has been performed to induce ischemia. [1][2][3][4][5] We think that our new technique has several advantages over these two methods. Unlike CL, our method makes it possible to lower the PAP to the targeted level and to inhibit the initial rise in the PAP during cross-clamping.…”
Section: Discussionmentioning
confidence: 99%
“…However, monitoring of the cerebrospinal uid pressure alone is not supposed to prevent all spinal cord ischemic injuries (78). Controversial experimental (76,79,80) and clinical results (77,(80)(81)(82)(83) have been reported with monitoring of cerebrospinal uid pressure and its drainage, and these are probably due to the fact that several other factors also in uence spinal cord perfusion pressure, and not necessarily result in an increase of cerebrospinal uid pressure.…”
Section: Cerebrospinal Uid Pressure Monitoring and Drainagementioning
confidence: 99%
“…Cooling of the spinal cord has been carried out in the experimental and clinical setting by perfusion through the intercostal and lumbar vessels (122,123), subdural space (57,78), and epidural space (77,124,125), by applying a cold pack on the lumbar area (123,126) and through retrograde venous perfusion of the spinal cord (127)(128)(129). Cambria et al (77) recently reported a series of 170 patients who underwent descending or thoracoabdominal aortic aneurysm repair employing the adjuncts of epidural cooling, reimplantation of intercostal arteries from T8 to L1 by an inclusion botton or beleved anastomosis (but only in 61% of patients with type I and II aneurysms), and cerebrospinal uid pressure monitoring and drainage to maintain its pressure below 12 mmHg, followed by passive cerebrospinal uid drainage for 48 h. The authors succeeded in achieving a mean cerebrospinal uid temperature of 26.4°C during aortic cross-clamping, the mean core temperature being 35.0°C.…”
Section: Hypothermiamentioning
confidence: 99%
“…Paraplegia has been reported at incidences ranging from 4.6 to 21% following TAAA repair [1][2][3][4]. Despite various refinements in surgical techniques and developments in adjunctive measures such as cerebrospinal fluid drainage, distal aortic perfusion, and spinal cord cooling [5][6][7], paraplegia remains a serious threat.…”
Section: Introductionmentioning
confidence: 99%